2014
DOI: 10.1016/j.jssc.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure refinement and chromate sorption characteristics of an Al-rich bayerite-based layered double hydroxide

Abstract: a b s t r a c t "Imbibition" of Zn 2 þ ions into the cation vacancies of bayerite-Al(OH) 3 and NO 3 À ions into the interlayer gallery yields an Al-rich layered double hydroxide with Al/Zn ratio $3. NO 3 À ions are intercalated with their molecular planes inclined at an angle to the plane of the metal hydroxide slab and bonded to it by hydrogen bonds. Rietveld refinement of the structure shows that the monoclinic symmetry of the precursor bayerite is preserved in the product, showing that the imbibition is top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 14 publications
2
25
1
1
Order By: Relevance
“…The increase of the initial Cu:Al molar ratio facilitated the formation of thicker LDHs; the intensity of the reflections increased and split at around 20 and 22 • 2θ for the CuAl 4 -ClO 4 − -LDH, which is a common phenomenon. This effect was already observed for LiAl 2 - [26], ZnAl 4 -LDHs [27] and, in our recent work, for NiAl 4 -ClO 4 − -LDH and for NiAl 4 -NH 2 SO 3 − -LDH [24]. The FT-IR of the solids also verified the formation of phase-pure CuAl 4 -X n− -LDHs.…”
Section: Optimization Of the Synthesis Parameters For The Preparation Of Cual4-ldhssupporting
confidence: 81%
“…The increase of the initial Cu:Al molar ratio facilitated the formation of thicker LDHs; the intensity of the reflections increased and split at around 20 and 22 • 2θ for the CuAl 4 -ClO 4 − -LDH, which is a common phenomenon. This effect was already observed for LiAl 2 - [26], ZnAl 4 -LDHs [27] and, in our recent work, for NiAl 4 -ClO 4 − -LDH and for NiAl 4 -NH 2 SO 3 − -LDH [24]. The FT-IR of the solids also verified the formation of phase-pure CuAl 4 -X n− -LDHs.…”
Section: Optimization Of the Synthesis Parameters For The Preparation Of Cual4-ldhssupporting
confidence: 81%
“…However, their sample contained excess Zn (Al:Zn ≈ 3:1), which was modeled as Zn substitution on one of the four crystallographic Al sites and with substantial Zn/Al vacancies . Williams et al reported the structure of ZnAl 4 -LDH with nitrate, but the sample was heated at 175 °C to remove interlayer water, and a number of structural ambiguities remain. , Recently, Pushparaj et al reported a Rietveld refined structure of a ZnAl 4 -LDH sample that contained no crystalline impurities according to PXRD. Several structural models were validated using input from 27 Al solid-state NMR spectroscopy (SSNMR) and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…, and Eqs. 1-317 ) corresponds to 2.62(5) H2O, 5.99(5) OH, and 0.99(5) SO4 , respectively based on a composition of ZnO + 2 Al2O3 for the end product. Thus, a formula of ZnAl4(OH)5.99(5)(SO4)⋅2.62(5) H2O is derived, i.e., a stoichiometric sample within the 3-3.3 interlayer water molecules and positional disorder for one of the interlayer O site from single crystal XRD,15 i.e., a variable interlayer water content.…”
mentioning
confidence: 99%
“…20 Due to their high charge density of the sheets and the exchangeability of the interlayer anions, LDHs have been employed for removing different anions by both surface adsorption and anion exchange. [21][22][23][24] Some studies of hexavalent chromium adsorption by MgAl-LDH, 23,25 Mg 3Àx Ca x Fe-LDH, 24 MgAlFe-LDH, 26 ZnAl 4 -LDH, 27 CoBi-LDH 28 and MgAl-, NiAl-, ZnAl-LDHs 29 were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%